Kinesiology taping does not change fibularis longus latency time and postural sway. Issue 1 (January 2016) - Correia, Christophe; Lopes, Susana; Gonçalves, Rafael; Torres, Rui; Pinho, Francisco; Gonçalves, Pedro; Rodrigues, Mário; Costa, Rui; Lopes, Mário; Ribeiro, Fernando
Summary: Background: Kinesiology tape seems to improve muscle force, although little is known regarding its effect on latency time and postural sway. Objectives: To examine the effects of kinesiology taping on fibularis longus latency time and postural sway in healthy subjects. Methods: Thirty participants were equally randomized into three groups, two experimental groups receiving kinesiology tape (EG1, from origin to insertion; EG2, from insertion to origin) and a control group. Before and 20-min after the intervention, postural sway was assessed on a force platform and fibularis longus latency time was recorded with surface electromyography during a sudden inversion perturbation. Results: At baseline, no differences were found between groups regarding age, anthropometrics variables, postural sway and fibularis longus latency time. In both experimental groups, the application of tape did not change postural sway and fibularis longus latency time (EG1: 93.7 ± 15.0 to 89.9 ± 15.6 ms; EG2, 81.24 ± 14.21 to 81.57 ± 16.64, p < 0.05). Also, no changes were observed in the control group. Conclusion: Kinesiology tape seems not to enhance fibularis longus reaction time and postural sway in young healthy subjects.